Cerebral Sinus Venous Thrombosis due to Asparaginase Therapy - Youssef Alsaid; Shamshad Gulab; Mohammed Bayoumi; Saleh Baeesa (Case Reports in Hematology)
We report a 9-year-old boy with acute lymphoblastic leukemia (ALL) in high-risk group who suffered from left sided focal seizures and ipsilateral hemiparesis during his induction with Asparaginase chemotherapy. Superior sagittal sinus thrombosis and right frontal hemorrhage were demonstrated on brain magnetic resonance imaging (MRI) scans . Anticoagulation was initiated with unfractionated heparin and switched to low molecular weight heparin after 3 weeks and continued for 6 months. At one-year followup, he had complete response to chemotherapy for ALL, with residual mild left hemiparesis, and his MRI scans revealed recanalized venous sinuses. The case highlights the importance of considering cerebral venous thrombosis as a complication of Asparaginase therapy.